Between Informal Marriage and Legal Certainty: Determining Marital Status through Isbat Nikah at the South Jakarta Religious Court - Kartika Sari; Azmi Islami; Delpa Firdaus (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The phenomenon of unofficial marriages, or